Unraveling the dynamic changes of volatile compounds during the rolling process of Congou black tea via GC-E-nose and GC–MS - Wang, Qiwei; Shi, Daliang; Hu, Jiajing; Tang, Jiahao; Zhou, Xianxiu; Wang, Lilei; Xie, Jialing; Jiang, Yongwen; Yuan, Haibo; Yang, Yanqin (Frontiers in Sustainable Food Systems, 2024)
Rolling plays an important role in shaping the characteristic quality of black tea. However, the dynamic alterations in volatile compounds during the rolling process remain unclear, which hampers the quality control of black tea. In this study, the dynamic changes of volatile compounds in Congou black tea throughout the rolling process were explored by a combination of GC-E-Nose and GC-MS analysis. A total of 82 volatile compounds including eight categories were identified in Congou black tea during the rolling process. The most abundant volatiles were aldehydes, alcohols, and esters. The results of PCA and PLS-DA revealed significant alterations in the volatile profiles, particularly at the 15-min rolling stage. Through the integration of variable importance in the projection > 1 and p < 0.05, 21 volatile compounds were pinpointed as pivotal volatiles responsible for distinguishing diverse rolling processes. According to their pathways, glycoside-derived volatiles (GDVs) (such as linalool and geraniol) and fatty acid-derived volatiles (FADVs) (such as (Z)-2-hexen-1-ol and hexanal) highlighted the pivotal role in the formation of the aroma of black tea during rolling process. GDVs, characterized by floral, honeyed, and fruity aromas, reached the lowest point at 35-min rolling and subsequently rebounded. FADVs exhibited an ascending trajectory during the initial 15-min rolling, followed by a downward trend. These findings provide invaluable insights into the aroma evolution during the rolling stage, offering strategies for enhancing the aroma quality of Congou black tea.